Serum estradiol levels and bone mineral density in postmenopausal women - Mawi, Martiem (Universa Medicina, 2010)
Postmenopausal women are at high risk of disease, such as coronary heart disease, stroke, malignancies, dementia and osteoporosis. This is due to decreased levels of estrogen/estradiol, produced mainly in the ovaries, leading to reduced bone mineral density (BMD), which is the gold standard for diagnosis of osteoporosis. The purpose of the present study was to determine the relationship between serum estradiol levels and BMD in postmenopausal women. The study, which was of cross-sectional design, involved 184 postmenopausal women meeting the inclusion criteria, viz. healthy postmenopausal women aged between 47 and 60 years having taken no hormonal medications in the previous 3 years. The subjects were assessed for anthropometric and biochemical characteristics, including BMD and serum estradiol levels. BMD was measured at the lumbar spine, right femoral neck and at the distal radius by the dual-energy X-ray absorptiometry (DXA) instrument. The mean serum estradiol concentration was 7.54 Â± 4.65 pg/ml, while in 49.5% of the subjects the estradiol concentration was Â£ 5 pg/ml. In postmenopausal women with estradiol concentrations of > 5 pg/ml, a significant positive relationship was found between BMD and the T-scores for the femoral neck. Thus the higher the serum estradiol levels, the higher the BMD values for femoral neck region. In conclusion, the results of this study point to estradiol levels as a major factor in determining the BMD values in postmenopausal women.